Kajian Etnopedagogi: Seba dalam Masyarakat Baduy - Adang Heriawan; Denny Soetrisnaadisendjaja; Siska Hidayati (Hermeneutika : Jurnal Hermeneutika, 2018)
Abstrak Etnopedagogi memandang pengetahuan atau kearifan lokal (local nowledge, local wisdom) sebagai sumber inovasi dan keterampilan yang dapat diberdayakan demi kesejahteraan masyarakat. Selanjutnya, Hafid, et al (2015) menegaskan bahwa “...Ethnopedagogy is an educational practice based on local wisdom in various fields such as medicinal treatment, selfdefence art, living environment, agriculture, economy, government, calendar system, and etc. Ethnopedagogy perceives that knowledge or local wisdom as the source of innovation and skill that can be empowered for the sake of the society’s welfare...”. Pendapat ini menegaskan bahwa etnopedagogi mengangkat nilai- nilai kearifan lokal sebagai bagian penting dalam proses pendidikan, sebagai bagian dari proses pembudayaan. Selain itu, dalam ekskalasi interaksi sosial yang semakin dinamis karena berbagai isyu yang akan menjadi pemicu munculnya konflik, juga menempatkan etnopedagogi sebagai model pembelajaran berbasis perbedaan dalam upaya menemukan upaya penyatuan dalam perbedaan itu sendiri. Hal ini sebagaimana diungkapkan oleh Guzaliya Zh Fahrutdinova (2016) dalam salah satu kajian empiriknya menjelaskan sebagai berikut : “ With the increased tension in human relations, in a burst of misundertsanding, ethnic conflicts, which have proliferated in a new socio-cultural environment, the study of processes of interaction in multi-ethnic educational environment and upbringing, the emerging national identity for centuries, actualizes the importance of contemporary problems of etnopedagogical education”.Pendidikan melalui pendekatan etnopedagogi, melihat pengetahuan lokal sebagai sumber inovasi dan keterampilan yang dapat diberdayakan (Priadi Surya, 2011) untuk proses pembelajaran yang sedang dan akan berlangsung. Kearifan lokal merupakan ungkapan budaya yang khas, didalamnya terkandung tata nilai, etika, norma, aturan dan ketrampilan suatu komunitas dalam memenuhi tantangan keberlanjutan kehidupannya (Suswandari, 2017). Bahkan tidak jarang, kearifan lokal sering digunakan sebagai lokal decisión making, sebagaimana berlaku dalam bidang pengelolaan sumber daya alam dan berbagai aktivitas sosial lainnya dalam lingkungan kehidupan masyarakat.Kata Kunci, Etnopaedagogi, seba, masyarakat dam baduy.Abstract Ethnopedagogy views knowledge or local wisdom (local knowledge) as a source of innovation and skills that can be empowered for the welfare of society. Furthermore, Hafid, et al (2015) asserted that "... Ethnopedagogy is an educational practice based on local wisdom in various fields such as medicinal treatment, self-defense art, living environment, agriculture, economy, government, calendar system, and etc. Ethnopedagogy perceives that knowledge or local wisdom as the source of innovation and skill that can be empowered for the sake of the society ... ". This opinion emphasizes that ethnagagogy elevates the values of local wisdom as an important part of the education process, as part of the civilization process. In addition, in the escalation of increasingly dynamic social interactions because various issues that will trigger the emergence of conflict, also places ethnopedagogy as a difference-based learning model in an effort to find efforts to unite in the differences themselves. This as revealed by Guzaliya Zh Fahrutdinova (2016) in one of his empirical studies explains as follows: "With the increase in human relations tension, in a burst of misunderstanding, ethnic conflicts, which have proliferated in a new socio-cultural environment, the "The study of interaction in multi-ethnic educational environment and upbringing, the emerging national identity for centuries, actualizes the importance of contemporary problems of ethnoagogical education".Education through the ethopedic approach, sees local knowledge as a source of innovation and empowerable skills (Priadi Surya, 2011) for the ongoing and ongoing learning process. Local wisdom is a distinctive cultural expression, in which the values, ethics, norms, rules and skills of a community are contained in meeting the challenges of sustainability of life (Suswandari, 2017). In fact, not infrequently, local wisdom is often used as a local decisión making, as applicable in the field of natural resource management and various other social activities in the community's living environment.Keywords, Etnopaedagogi, seba, community and baduy.